Antimicrobial stewardship in Scotland: impact of a national programme - Nathwani Dilip (Antimicrobial Resistance and Infection Control, 2012)
Abstract Backgound The Scottish Antimicrobial Prescribing Group (SAPG) was established by the Scottish Government in 2008 to lead the first national initiative to actively address antimicrobial stewardship. Healthcare associated infection (HAI) is a priority in Scotland and the work of SAPG contributes to the national HAI Delivery Plan. SAPG's early work has focused on restricting the use of antibiotics associated with a high risk of Clostridium difficile infection (CDI) and development of national prescribing indicators to support reduction of CDI. Findings Scottish Antimicrobial Prescribing Group has developed prescribing indicators for hospital and primary care, which are measured and reported in all 14 NHS board areas. Improvement in compliance with the indicators has been demonstrated with resultant reductions in CDI rates and no adverse effect on mortality or antimicrobial resistance patterns. Conclusions The establishment of a Scottish national antimicrobial stewardship programme has made a significant contribution to the HAI agenda, particularly in relation to CDI. The programme is supported by local antimicrobial teams, a national framework for education, surveillance of antimicrobial use and resistance and sharing of data for improvement. Antimicrobial stewardship has been integrated with other national programmes on patient safety and quality improvement.